How Does Lexical Access Fit into Models of Word Reading?. (4th July 2022) - MacKay, Elizabeth J.; Conrad, Nicole; Deacon, S. Hélène
ABSTRACT: Skilled reading requires fast and accurate access to previously encountered words stored in memory. Yet, little research addresses skills that support such lexical access. Based on theoretical predictions, one skill that may support lexical access is orthographic knowledge. Thus, our goal was to investigate the relation between lexical access and orthographic knowledge. We addressed this research question in a sample of 104 English-speaking fourth grade children. We assessed lexical access with an experimenter-created measure of timed word recognition; word reading efficiency with the TOWRE Sight Word Efficiency subtest; and lexical and sublexical orthographic knowledge with real and nonword orthographic choice tasks, respectively. We controlled for other reading related skills, including nonverbal ability and phonological awareness. A confirmatory factor analysis confirmed that lexical access and word reading efficiency are separate constructs. A subsequent linear regression revealed a concurrent relation between sublexical orthographic knowledge and lexical access beyond controls. Results highlight a unique place for lexical access in reading development theory and help us better understand the specific skills required to read quickly and accurately.